1969
DOI: 10.1021/bi00833a004
|View full text |Cite
|
Sign up to set email alerts
|

Uncatalyzed hydrolysis of deoxyuridine, thymidine, and 5-bromodeoxyuridine

Abstract: The N-glycosyl bonds of deoxyuridine, thymidine, and 5-bromodeoxyuridine undergo slow hydrolysis in aqueous solution, pH 3-7. The reaction rates are independent of the pH in this range, and of the nature and concentration of the buffer. The reactions have positive entropies of activation. A linear correlation exists between the logarithms of the rate constants for the three nucleosides and the ionization constants for the 1-protons of the corresponding bases. It is pro-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
100
0

Year Published

1970
1970
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(109 citation statements)
references
References 30 publications
(39 reference statements)
9
100
0
Order By: Relevance
“…Under these conditions, proton NMR and UV spectroscopic analysis showed that both substrates are converted quantitatively to thymine, with no significant degradation of the pyrimidine ring. The hydrolysis of thymidine to thymine, as indicated by UV analysis, was observed earlier in neutral and acid solution (8). Table 1 summarizes the rate constants, enthalpies, and entropies of activation for diester hydrolysis observed in this study and earlier work.…”
Section: Resultssupporting
confidence: 65%
“…Under these conditions, proton NMR and UV spectroscopic analysis showed that both substrates are converted quantitatively to thymine, with no significant degradation of the pyrimidine ring. The hydrolysis of thymidine to thymine, as indicated by UV analysis, was observed earlier in neutral and acid solution (8). Table 1 summarizes the rate constants, enthalpies, and entropies of activation for diester hydrolysis observed in this study and earlier work.…”
Section: Resultssupporting
confidence: 65%
“…44,56 Indeed, the N1 and N3 acidities of uracil differ by 14 kcal/mol in the gas phase, 44,46,56 whereas they are nearly equivalent in aqueous solution. 22 Thus, as indicated by previous studies, gas-phase acidities can be informative regarding the leaving ability of a nucleobase within a hydrophobic active site, and may be relevant to the mechanism of substrate discrimination. 44,71 We therefore examined the dependence of hTDG activity on N1 acidity in a non-polar environment by calculating the gas phase N1 acidities of the nucleobases at 298 K (ΔG acid,g , Table S1, Supporting Information).…”
Section: Linear Free Energy Relationships For N-glycosidic Bond Hydromentioning
confidence: 85%
“…A plot of log(k non ) versus pK a N1 for the spontaneous hydrolysis of dU, dT, and 5-Br-dU at pH 6.5 and 75 °C has a slope of β lg = −0.86 ± 0.03, 22,75 and the same value (β lg = −0.86 ± 0.05) is obtained using k non values extrapolated to 22 °C for dU, dT, 5-F-dU, 5-Cl-dU, and 5-Br-dU ( Figure S3, Supporting Information). These β lg values, together with the observed low and positive activation entropies, 22 are consistent with a highly dissociative transition state for the nonenzymatic reaction, 22,23,76 although it was concluded from computational studies that the mechanism is concerted (A N D N ) rather than stepwise (D N *A N ). 77 The more negative β lg = −1.6 observed for hTDG indicates that the transition state (TS) of the enzymatic reaction is more sensitive to the development of negative charge on N1 of the leaving group base than is the TS of the non-enzymatic reaction.…”
Section: Implications Of the Brønsted-type Lfer For The Mechanism Of mentioning
confidence: 99%
“…The substrate reactivity (N-glycosidic bond stability) also depends on the C5 substituent. Thus, for the hTDG-catalyzed and non-catalyzed reactions, the rate depends on the leaving ability of the departing nucleobase (20,(42)(43)(44). The electron withdrawing halogens enhance the leaving ability of uracil, whereas the electron donating methyl group suppresses it.…”
Section: Discussionmentioning
confidence: 99%